Species-specific biodegradation of sporopollenin-based microcapsules - Fan, Teng-Fei (2019)
Sporoderms, the outer layers of plant spores and pollen grains, are some of the most robust biomaterials in nature. In order to evaluate the potential of sporoderms in biomedical applications, we studied the biodegradation in simulated gastrointestinal fluid of sporoderm microcapsules (SDMCs) derived from four different plant species: lycopodium (Lycopodium clavatum L.), camellia (Camellia sinensis L.), cattail (Typha angustifolia L.), and dandelion (Taraxacum officinale L.). Dynamic image particle analysis (DIPA) and field-emission scanning electron microscopy (FE-SEM) were used to investigate the morphological characteristics of the capsules, and Fourier-transform infrared (FTIR) spectroscopy was used to evaluate their chemical properties. We found that SDMCs undergo bulk degradation in a species-dependent manner, with camellia SDMCs undergoing the most extensive degradation, and dandelion and lycopodium SDMCs being the most robust.